Композиционные материалы на основе поливинилхлорида для изоляции кабельно-проводниковой продукции. Теплофизические, реологические и электрофизические свойства (Електротехніка і електромеханіка, 2012)
The article presents results of theoretical and experimental research on polymeric compositions development on the basis of PVC of different producers for cable-conductor insulation to provide complex technical properties as for manufacturability and performance figures. The basic distinctions of thermophysical, reologycal and electrophysical characteristics are studied depending on the PVC used.